Morphologic alterations of the fear circuitry: the role of sex hormones and oral contraceptives - Brouillard, Alexandra; Davignon, Lisa-Marie; Turcotte, Anne-Marie; Marin, Marie-France (Frontiers in Endocrinology, 2023)
Background: Endogenous sex hormones and oral contraceptives (OCs) have been shown to influence key regions implicated in fear processing. While OC use has been found to impact brain morphology, methodological challenges remain to be addressed, such as avoiding selection bias between OC users and non-users, as well as examining potential lasting effects of OC intake.Objective: We investigated the current and lasting effects of OC use, as well as the interplay between the current hormonal milieu and history of hormonal contraception use on structural correlates of the fear circuitry. We also examined the role of endogenous and exogenous sex hormones within this network.We recruited healthy adults aged 23-35 who identified as women currently using (n=62) or having used (n=37) solely combined OCs, women who never used any hormonal contraceptives (n=40), or men (n=41). Salivary endogenous sex hormones and current users' salivary ethinyl estradiol (EE) were assessed using liquid chromatography -tandem mass spectrometry. Using structural magnetic resonance imaging, we extracted surface-based gray matter volumes (GMVs) and cortical thickness (CT) for regions of interest of the fear circuitry. Exploratory whole-brain analyses were conducted with surface-based and voxel-based morphometry methods.Results: Compared to men, all three groups of women exhibited a larger GMV of the dorsal anterior cingulate cortex, while only current users showed a thinner ventromedial prefrontal cortex. Irrespective of the menstrual cycle phase, never users exhibited a thicker right anterior insular cortex than past users. While associations with endogenous sex hormones remain unclear, we showed that EE dosage in current users had a greater influence on brain anatomy compared to salivary EE levels and progestin androgenicity, with lower doses being associated with smaller cortical GMVs. Discussion: Our results highlight a sex difference for the dorsal anterior cingulate cortex GMV (a fearpromoting region), as well as a reduced CT of the ventromedial prefrontal cortex (a fear-inhibiting region) specific to current OC use. Precisely, this finding was driven by lower EE doses. These findings may represent structural vulnerabilities to anxiety and stress-related disorders. We showed little evidence of durable anatomical effects, suggesting that OC intake can (reversibly) affect fear-related brain morphology.